2020
DOI: 10.1102/2051-7726.2020.0008
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of medical student perception of surgical specialization with peer-assisted laparoscopic simulation: a pilot study

Abstract: Background: Although the pre-clinical years are pivotal in career path commitment for medical students, this phase of education is traditionally devoid of surgical exposure. Although peer-assisted learning and simulation are both validated methods of supplementing early exposure to medical specialties, their use in familiarizing students with modern surgical procedures remains minimal. We hypothesize that student-led laparoscopic simulation will result in significantly increased self-perception of surgical cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…Existing research has demonstrated that interactive workshops can bolster medical student interest and confidence in pursuing a surgical career. 16 While there is limited research describing the impact of surgical workshops on undergraduate premedical students, Vakayil et al 17 found that workshops can improve premedical students' perceived confidence in basic surgical knowledge, techniques, and teamwork. This improved a "Other" includes 1st or 2nd-year medical school students and those who were not currently enrolled in a medical school program at the time of survey (ie, undergraduates and recent graduates taking a "gap year").…”
Section: Discussionmentioning
confidence: 99%
“…Existing research has demonstrated that interactive workshops can bolster medical student interest and confidence in pursuing a surgical career. 16 While there is limited research describing the impact of surgical workshops on undergraduate premedical students, Vakayil et al 17 found that workshops can improve premedical students' perceived confidence in basic surgical knowledge, techniques, and teamwork. This improved a "Other" includes 1st or 2nd-year medical school students and those who were not currently enrolled in a medical school program at the time of survey (ie, undergraduates and recent graduates taking a "gap year").…”
Section: Discussionmentioning
confidence: 99%